2017
DOI: 10.1371/journal.pone.0174056
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric testing of the clinical networks engagement tool

Abstract: BackgroundClinical networks are being used widely to facilitate large system transformation in healthcare, by engagement of stakeholders throughout the health system. However, there are no available instruments that measure engagement in these networks.MethodsThe study purpose was to develop and assess the measurement properties of a multiprofessional tool to measure engagement in clinical network initiatives. Based on components of the International Association of Public Participation Spectrum and expert pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This variable-oriented strategy (Miles, Huberman, & Saldana, 2014) also facilitated cross-case analysis of the data during later stages of analysis. Phase 1 has been completed (Norris, Hecker, Rabatach, Noseworthy, & White, 2017; Norris, White, Nowell, Mrklas, & Stelfox, 2017). Phase 2 data are currently undergoing analysis, while data collection for Phase 3 has begun.…”
Section: Exemplar Studymentioning
confidence: 99%
“…This variable-oriented strategy (Miles, Huberman, & Saldana, 2014) also facilitated cross-case analysis of the data during later stages of analysis. Phase 1 has been completed (Norris, Hecker, Rabatach, Noseworthy, & White, 2017; Norris, White, Nowell, Mrklas, & Stelfox, 2017). Phase 2 data are currently undergoing analysis, while data collection for Phase 3 has begun.…”
Section: Exemplar Studymentioning
confidence: 99%
“…Within our program of research, SCN members at different organizational levels significantly differed in their views of the levels at which they were engaged: leaders were more engaged, while frontline clinicians were less engaged [ 46 ]. In this study, however, stakeholders across these same organizational groups defined engagement similarly—an unexpected finding.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, levels of engagement span from one-way information sharing to shared decision-making and stakeholder empowerment [ 40 – 42 ], a spectrum that involves increasingly participatory, transformative, and democratic processes [ 31 ]. While used to inform engagement with patient groups [ 43 ] and healthcare clinicians [ 44 , 45 ], there is minimal empirical evidence to support the use of these models in implementation [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, practitioners and researchers have identi ed co-production as a possible solution for several managerial issues. Indeed, recent studies have suggested co-production as a means to increase users' satisfaction and trust in service providers [1], enhance innovation [2], and improve the effectiveness and e ciency of products and services [3,4]. However, its fame has increased to such an extent that the co-production concept has 'enchanted' its audience [5]; it seems to have become a magic solution for both public and private challenges [6].…”
Section: Introductionmentioning
confidence: 99%